2009
DOI: 10.1080/13504500902918054
|View full text |Cite
|
Sign up to set email alerts
|

Integrating local knowledge with science and technology in management of soil, water and nutrients: implications for management of natural capital for sustainable rural livelihoods

Abstract: Harnessing local knowledge and practices for sustainable management of soil, water and nutrients is important for sustainable development. This work aims to understand soil productivity in traditional open-ridging practices and integrate scientific ideas and technologies into traditional practices for enhancing management of soil productivity. Participatory assessments, household surveys, field experiments, observations and analyses of outcomes were used. Participatory assessments revealed declining natural so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In this context, local experts should be identified [ 17 ] and their Local Ecological Knowledge (LEK) used to identify suitable tree species and guide future research [ 18 ]. Studies investigating LEK have confirmed that it is highly reliable and advocated for its greater integration into policy recommendations and conservation programs [ 19 , 20 ]. Furthermore, the comparison of farmers’ possession of LEK according to gender, ethnicity and farming practices can help refining our understanding of factors underpinning this LEK and improving policy recommendations [ 16 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, local experts should be identified [ 17 ] and their Local Ecological Knowledge (LEK) used to identify suitable tree species and guide future research [ 18 ]. Studies investigating LEK have confirmed that it is highly reliable and advocated for its greater integration into policy recommendations and conservation programs [ 19 , 20 ]. Furthermore, the comparison of farmers’ possession of LEK according to gender, ethnicity and farming practices can help refining our understanding of factors underpinning this LEK and improving policy recommendations [ 16 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLM can be implemented to reduce soil and SOC loss by various runoff interception techniques; forms of physical barriers designed to directly break the structural connectivity components in the landscape and, in doing so, act as rainwater harvesting (RWH) methods. These methods can draw upon in situ, micro-scale structures, capturing water and sediment at the planting zone [64][65][66] or be larger, macro-scale structures, which are designed to channel water into the cropped area [64,67]. Both approaches have the capacity to increase and maintain SOC by reducing soil loss, capturing sediment and associated SOM, and by improving moisture and nutrient retention, which benefits microbial pools and biomass.…”
Section: Common Slm Methods To Maintain and Enhance Socmentioning
confidence: 99%
“…This suggests that farmers are able to observe some land management impacts on soils but also require information from conventional soil testing for a comprehensive understanding of impacts that are not easily observed. As noted by Malley et al (2009), it will be highly beneficial for land managers to integrate scientific knowledge with their local knowledge of the agro-ecosystem. This can be achieved by improving farmers' access to relevant information about correct SWC practices and their non-visible impacts via strengthening of the agricultural extension services and establishing strong links between farming communities and research institutions where soils can be tested and advice provided (Nyanga et al, 2016).…”
Section: Benefits Of Combining Conventional Soil Testing With Farmers...mentioning
confidence: 99%